If it's not what You are looking for type in the equation solver your own equation and let us solve it.
u in (-oo:+oo)
(2/3)*u-(8/9) = -7/5 // + -7/5
(2/3)*u-(8/9)-(-7/5) = 0
(2/3)*u-8/9+7/5 = 0
2/3*u+23/45 = 0 // - 23/45
2/3*u = -23/45 // : 2/3
u = -23/45/2/3
u = -23/30
u = -23/30
| 6x=ln(10/9) | | 4x+-2y=18 | | 4k(-3mk)= | | 2/5×25 | | 5+7x(3+2)-16= | | 3x+4+x=4-x | | 36b+-10=-6 | | 45=5x-9+x | | -(1/7×3/2)= | | Y/10=9/4 | | 4c-16=8 | | -12u+7=-1 | | 3x^2-7x+3=2x^2-4x+3 | | j-3=7+6j | | 16/1 | | y^2-2xy+3=0 | | 7p-10=6p | | 5/50=t/4 | | 56y+5=13 | | 5/75=t/10 | | P/8=-51/24 | | 3/2=n/10 | | -14+49v=42 | | x^2=-54-15x | | 5/x=55/22 | | .5(8x-43+10)=2x | | 36+16u=52 | | -3(5z-12)= | | -x+179=229 | | 2/3(5x) | | 18x-3=20x-16 | | f(-7)=3y-5 |